1992
DOI: 10.1007/bf00400488
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to Type 1 (insulin-dependent) diabetes mellitus in Spanish patients correlates quantitatively with expression of HLA-DQ ? Arg 52 and HLA-DQ ? non-Asp 57 alleles

Abstract: HLA-DQ alpha and beta alleles were chosen as the most sensitive Type 1 (insulin-dependent) diabetes mellitus susceptibility markers for evaluating the disease associations and Type 1 diabetes risk in a population-based registry from Madrid. The absence of aspartic acid in position 57 of the DQ beta chain (non-Asp 57), and the presence of arginine in position 52 of the DQ alpha chain (Arg 52) were found to be reliable markers of Type 1 diabetes susceptibility among the Spanish population, with significantly hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 44 publications
4
22
0
Order By: Relevance
“…It was hypothesized that the presence of aspartic acid at position 57 of the DQ-beta chain determines protection from diabetes (Morel et al, 1988). Further reports suggested that an arginine at position 52 of the DQ-alpha chain determined susceptibility to type IA diabetes, as it is found on the DQA1*0301-DQB 1*0302 and DQA I*050 1 -DQB 1*020 1 haplotypes (Gutierrez-Lopez, 1992;Khalil et al, 1990Khalil et al, ,1992. However, the DQAl*0401-DQB1*0402 haplotype is also associated with diabetes risk.…”
Section: Mechanisms Of Diabetogenicity Of Hla Moleculesmentioning
confidence: 99%
“…It was hypothesized that the presence of aspartic acid at position 57 of the DQ-beta chain determines protection from diabetes (Morel et al, 1988). Further reports suggested that an arginine at position 52 of the DQ-alpha chain determined susceptibility to type IA diabetes, as it is found on the DQA1*0301-DQB 1*0302 and DQA I*050 1 -DQB 1*020 1 haplotypes (Gutierrez-Lopez, 1992;Khalil et al, 1990Khalil et al, ,1992. However, the DQAl*0401-DQB1*0402 haplotype is also associated with diabetes risk.…”
Section: Mechanisms Of Diabetogenicity Of Hla Moleculesmentioning
confidence: 99%
“…Genetic predisposition to IDDM was found to increase proportionally with the number of both a-and/3-susceptible alleles present at the cell surface of activated T and B cells in a given individual [63,88].…”
Section: The Genetic Componentmentioning
confidence: 98%
“…Recently, a new, more sensitive approach was conceived in which two diallelic systems are used for determining the IDDM association [31,33]. The first marker determination examines position 57 of the DQ fl-chain for Asp/non-Asp status, while the second determination examines position 52 of the DQ e-chain for Arg/non-Arg status.…”
Section: The Hla Moleculementioning
confidence: 99%
“…It is interesting, however, to mention that there is a hierarchical scale of susceptibility within both the group of the non-Asp 57 and the group of Arg 52 alleles, as the susceptibility conferred by the individual alleles of each group is not equally strong. The same consideration is valid for the groups of the Asp 57 and non-Arg 52 alleles and the degree of protection they confer [31,33,62]. In the heterozygotes, a sort of competition for the antigen might take place between different molecules, with certain alleles of one group prevailing in their effects over alleles of the other group.…”
Section: The Hla Moleculementioning
confidence: 99%